The Campus Canopy, 1940-04-19 - The Campus Canopy, The Georgia State Woman's College (The Georgia State Woman's College, 1940)
The Campus Canopy, April 12, 1940. Vol. 6, No. 19. -- “First Lady ’ Will Be Presented Tonight At 8:30 -- Dr. Smith To Give Series Of Lectures -- Martha Wilkes Voted As “Fashion Plate” Of G.S.W.C. -- Reid Elected ’41 President Of G.A.F.C.W -- Christian To Be President Philharmonic -- Freshman Honor Society Invites 12 New Member -- 7 Students Are Daughters Of GSWC Alumnae -- “Johnny” Tells All From A Fortune Telling Book -- Williams Elected To GSCC Office -- I.R.C. Elects 1940 Officers
Digitized from original print, Valdosta State University Archives and Special Collections, January 10, 2017.
Keywords: The Campus Canopy; The Georgia State Woman's College; Valdosta State University; Valdosta State College; GSWC; VSC; VSU; 1940; 1940s